FACTORS INFLUENCING ON THE MORTALITY IN PATIENTS WITH OBLITERATING DISEASES OF LOWER LIMB ARTERIES - A. N. Sumin; M. A. Kosova; Ju. D. Medvedeva; A. V. Shcheglova; O. I. Rajh; S. A. Makarov; G. V. Artamonova; L. S. Barbarash (Столичная издательская компания, 2017)
Aim. To study the risk factors associated with the fatal outcome in patients with obliterating diseases of the lower extremities arteries at the stage of outpatient observation.Material and methods. The study included 467 patients (381 men and 86 women, the median age - 63 years [59;70]) with obliterating atherosclerosis of lower limb arteries >50%. Patients were examined in the framework of the current registry on the basis of the Kemerovo Cardiology Center for the period from 2009 to 2013. The examination included the dynamic observation of an angiosurgeon and a cardiologist, the determination of instrumental and laboratory indicators. During 3 years of follow-up, 42 deaths were registered (8.99% of the total number of patients), including 28 (65%) ones due to cardiovascular diseases. Patients were divided into two groups - with a fatal outcome (9%) and without it (91%).Results. The lethal outcome was associated with the male gender (83%), disability (69.8%), retirement status (85.5%), higher incidence of previously diagnosed myocardial infarction (38.5%), angina pectoris (66.6%), stroke or transient ischemic attack (19%). Lesions of two (86%) and three arterial basins (36%) and significant coronary bed lesions (74%) were more frequent in patients with lethal outcome, they were characterized by a longer smoking experience (17.9 years) and hypertension (14.5 years). Surviving patients were more likely to undergo reconstructive surgeries on lower limb arteries (26.5%).Conclusion. Factors associated with death in patients with obliterating diseases of the lower extremities arteries were angina pectoris [odds ratio (OR) 1.14, 95% confidence interval (CI) 1.04-1.43; p=0.041), smoking experience (OR 1.28, 95% CI 1, 8-3,24; p=0,023), the duration of hypercholesterolemia (OR 2.01, 95% CI 0.35-4.12; p=0.012) and intermittent claudication (OR 2.01, 95% CI 0.35-4.12; p=0.041), presence of coronary artery stenosis ≥50% (OR 3.21, 95% CI 2.02-6.14; p=0.031), atherosclerosis of two or more arterial basins ≥50% (OR 3.43, 95% CI 3.46-5.52; p=0.004), the presence of a history of myocardial infarction (OR 2.12, 95% CI 0.75-6.02; p=0.043), and stroke (OR 2.23, 95% CI 2.05-4.21; p=0.021). To improve the effectiveness of secondary prevention in these patients it is advisable to use new organizational approaches at the outpatient stage of their management.